Sociopragmatic Review of Teacher Tutoring in Learning Interactions in Senior High School - Maryanto, Prasetyo Budi; Rokhman, Fathur (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
In classroom interaction, teachers always use speech. The instructor has the intention that the students take action by the wishes of the teacher. The purpose of this research is to find and to describe the form, purpose, implicature, and function of teacher speech illocutionary in an interaction of learning in Senior High School. The data were collected by using Simak Libat Cakap (SLC) technique, Simak Bebas Libat Cakap (SBLC) technique and interview technique using skill and fishing technique. Data analysis is done by contextual analysis method. The form of teaching teacher illocutionary contained in the interaction of learning in high school tangible direct speech and indirect speech. The purpose of the illocutionary of teacher's speech in the interaction of learning in high school is to inform the activities at school, to explain the instruction of the activity, to define the term, to ask the lesson material, to justify the inappropriate student answer, to draw the students attention to the lesson, and to instruct the students to do something and ordered not to do anything. The implication of teacher's speech in the interaction of learning in Senior High School is the conventional implicature based on the agreement of the student with the teacher at the beginning of the activity and the unconventional implication based on the context and the teacher's speech in a speech event. The function of the teacher's teacher's illocutionary in the interaction of learning in Senior High School is representative of the truth of teacher's speech, directive directive directive, expressive showing teacher's expression, commissive in the form of offering teacher promise to students, a declaration in the form of punishment sentence to the students.